1993
DOI: 10.1128/jb.175.19.6276-6286.1993
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of genes for an alternative nitrogenase in the cyanobacterium Anabaena variabilis

Abstract: Anabaena variabilis ATCC 29413 is a heterotrophic, nitrogen-fixing cyanobacterium that has been reported to fix nitrogen and reduce acetylene to ethane in the absence of molybdenum. DNA from this strain hybridized well at low stringency to the nitrogenase 2 (vnfDGK) genes of Azotobacter vinelandii. The hybridizing region was cloned from a lambda EMBL3 genomic library of A. variabilis, mapped, and sequenced. The deduced amino acid sequences of the vnfD and vnfK genes of A. variabilis showed only about 56% simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
167
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(170 citation statements)
references
References 55 publications
3
167
0
Order By: Relevance
“…Studies of the cyanobacterial genus Anabaena (a member of the same family as Nostoc, Nostocaceae) revealed that certain strains, all of which appear to be either obligate or facultative symbionts with plants, have an additional nitrogenase complex that is encoded by the vnf gene cluster (Thiel, 1993;Zehr et al, 2003;Raymond et al, 2004;Boison et al, 2006). The presence of the latter has also been inferred in a single strain of the cyanobacterial genus Nostoc (PCC 7422, isolated from plant tissue of Cycas sp.…”
Section: Introductionmentioning
confidence: 92%
“…Studies of the cyanobacterial genus Anabaena (a member of the same family as Nostoc, Nostocaceae) revealed that certain strains, all of which appear to be either obligate or facultative symbionts with plants, have an additional nitrogenase complex that is encoded by the vnf gene cluster (Thiel, 1993;Zehr et al, 2003;Raymond et al, 2004;Boison et al, 2006). The presence of the latter has also been inferred in a single strain of the cyanobacterial genus Nostoc (PCC 7422, isolated from plant tissue of Cycas sp.…”
Section: Introductionmentioning
confidence: 92%
“…However, the nif2 cluster, which lacks both the 11-kb and 55-kb elements, is expressed in vegetative cells, but only under anaerobic conditions, and in heterocysts (Thiel et al, , 1997. The vnf cluster codes for an alternative nitrogenase system containing a vanadium cofactor, instead of the usual molybdenum cofactor, and is expressed in the absence of molybdenum, but only in heterocysts (Thiel, 1993(Thiel, , 1996.…”
Section: Heterocyst Developmentmentioning
confidence: 99%
“…With regard to cyanobacteria, the occurrence of a vanadium nitrogenase has been inferred from both physiological and gene characterization studies of the heterocystous cyanobacterium Anabaena variabilis (15,36). Circumstantial evidence suggests that A. variabilis also possesses an iron nitrogenase (16), but this has not yet been corroborated by molecular data.…”
mentioning
confidence: 98%
“…A vanadium nitrogenase has also been detected only in Anabaena isolates from the water fern Azolla and in Nostoc sp. strain strain PCC6720 (Anabaenopsis circularis) (36). In addition, cyanobacteria may possess two sets of genetically different Mo-containing nitrogenases, a unique feature which has been clearly shown for A. variabilis (32,37).…”
mentioning
confidence: 99%